The Effect of Adding Probiotics on Microbial and Organoleptic Characteristics of Beef Burger Product - Asraa Yacoob Yousif (Journal of Global Pharma Technology, 2019)
The study examined the use of single and mixed probiotic isolates for the possibility of prolonging the preservation duration of meatballs in refrigeration. Chemical tests were conducted (free fatty acids, TBA and pH), sensory tests (color, flavor, juicy, tenderness and general acceptance), noting that the control sample was excluded from the experiment on the tenth day of conservation because the pH value exceeded the limit and according to the standard specifications. Samples of treatments with single and mixed probiotic isolates reached the allowable limits on the 11thday. A significant decrease in TBA and free fatty acid was observed in the single and mixed probiotic isolates compared with the control treatment during the preservation period. It was observed during the preservation period that the control sample was excluded from the experiment on the seventh day of preservation because the numbers of total bacteria and psychrophilic bacteria exceeded the permissible limits according to the standard specifications. The results of sensory evaluation showed a significant superiority of the probiotic isolates treated meat samples compared to the control sample, which improved all the sensory characteristics (color, flavor, juicy, tenderness and general acceptance). The highest of the sensory evaluation were in the mixed probiotic isolates treatments.Keywords: Probiotics, Organoleptic, Beef burger.